Effect of a delayed-action phenytoin preparation on blood phenytoin concentration - Bochner, F. (1972)
In a cross-over study in a group of epileptic patients it was shown that replacement of the evening dose of an ordinary phenytoin preparation with the same phenytoin dose in a delayed-action preparation produced no significant change in the next morning's mean blood phenytoin concentration. However, replacement of the entire daily dose of an ordinary phenytoin preparation with the delayed-action preparation did increase mean blood phenytoin levels after some days, possibly because the latter preparation contained an additional 6% active drug, as compared with the former. In most circumstances, it seems doubtful if the delayed-action preparation offers any advantage over ordinary phenytoin in treating epilepsy.